Oblicz wartość liczbową wyrażenia.

a) -y+8x-z-2x dla x=-2, y=6, z=-3
b) -8y-4z+x-y-2z+1 dla x=-0,5, y=-1, z=2
c) 9y-(7y+x)+(6x-7y) dla x=-2, y=3
d) (6a-8b-0,7)-(6,9+a-5b)+1,8 dla a=0,2 , b=0,1
e) 1/2 abc -(4ab+2abc)+(-bc+5ab) dla a=-2, b=1/2, c=-4

Mam tylko wyniki :(
a) -15
b) -2,5
c) -25
d) -5,1
e) -5

2

Odpowiedzi

2010-02-06T15:58:22+01:00
Będę już podstawiać
a)-6-16+3+4=-22+7=-15

b) 8-8-0,5+1-4+1=2-4,5=-2,5

c)27-(21-2)+(-12-21)=27-19-33=27-52=-25

d) (1,2-0,8-0,7)-(6,9+0,2-0,5)+1,8=-0,3-6,9-0,2+0,5+1,8=-7,4+2,3=-2,1

e) 2-(-4+8)+(2-5)=2-4-3=-5

2010-02-06T16:00:41+01:00
A) -y+8x-z-2x =6x-y-z=6*(-2)-6+3=-12-6+3=-15

b) -8y-4z+x-y-2z+1 =x-9y-6z+1= (-0,5)-9(-1)-6*2+1=-0,5+9-12+1=-12,5+10
=-2,5

c) 9y-(7y+x)+(6x-7y)=9y-7y-x+6x-7y=5x-5y=5*(-2)-5*3=-10-15=-25

d) (6a-8b-0,7)-(6,9+a-5b)+1,8 =6a-8b-0,7-6,9-a+5b+1,8=5a-3b-7,6+1,8=
5*0,2-3*0,1-7,6+1,8=1-0,3-7,6+1,8=1-7,9+1,8=-5,1

e) 1/2 abc -(4ab+2abc)+(-bc+5ab) =1/2abc-4ab-2abc-bc+5ab=ab-1,5abc-bc=
-2*0,5-1,5*(-2)*0,5*(-4)-0,5*(-4)= -1-6+2= -5